Formation of Light Absorbing Organo-Nitrogen Species from Evaporation of Droplets Containing Glyoxal and Ammonium Sulfate - Lee, Alex K. Y.; Zhao, Ran; Li, Richard; Liggio, John; Li, Shao-Meng; Abbatt, Jonathan. P. D. (ENVIRONMENTAL SCIENCE & TECHNOLOGY, 2013)
In the atmosphere, volatile organic compounds such as glyoxal can partition into aqueous droplets containing significant levels of inorganic salts. Upon droplet evaporation, both the organics and inorganic ions become highly concentrated, accelerating reactions between them. To demonstrate this process, we investigated the formation of organo-nitrogen and light absorbing materials in evaporating droplets containing glyoxal and different ammonium salts including (NH4)(2)SO4, NH4NO3, and NH4Cl. Our results demonstrate that evaporating glyoxal-(NH4)(2)SO4 droplets produce light absorbing species on a time scale of seconds, which is orders of magnitude faster than observed in bulk solutions. Using aerosol mass spectrometry, we show that particle-phase organics with high N:C ratios were formed when ammonium salts were used, and that the presence of sulfate ions promoted this chemistry. Since sulfate can also significantly enhance the Henry's law partitioning of glyoxal, our results highlight the atmospheric importance of such inorganic organic interactions in aqueous phase aerosol chemistry.